An evaluation of German active labour market policies: a review of the empirical evidence. Issue 4 (4th December 2018) - Zoellner, Moritz; Fritsch, Michael; Wyrwich, Michael
Abstract : Purpose: The purpose of this paper is to review the results of studies that investigate the most important active labour market policy (ALMP) measures in Germany. A focus is also on programmes devoted to foster entrepreneurship which can make important contributions to a country's growth and social welfare. Design/methodology/approach: The study relies on quantitative and qualitative assessments and a comparison of results of previous studies on ALMPs. Findings: The available evidence suggests that most ALMP measures increase labour market prospects of the participants. In particular, evaluations of the entrepreneurship promotion activities show high success rates as well as high cost efficiency. The bulk share of participants of entrepreneurship measures is still self-employed after several years and nearly one-third of these businesses had at least one employee. The authors mention problems regarding the evaluation of previous programmes and highlight future challenges of German ALMP. Originality/value: This is the first study on ALMP that has an extensive and explicit focus on entrepreneurship-promoting programs.